2nd generation IIUM buggy car – part II: fabrication - Mohiuddin, A. K. M. (IIUM Press, 2011)
This chapter provides the detailed information involved in the fabrication of the Second generation HUM buggy car project. Part II includes all details regarding the fabrication process Background research and literature review have been done in order to provide a basic referenc for this buggy car design. Analyses have been carried out extensively in developing an optimum fabrication for the buggy car. These analyses help to validate and determine the right setting 0f the dynamic aspect, especially for the suspension, braking and steering system. For the preliminary and detailed analyses finite element method and hand calculations are being used Collaboration between these forms of analyses is important in obtaining the overall accuracy 0f the car design